Implementing Efficiency within foreign language teaching - Slimane, Temagoult (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES, 2014)
لقد انتقل مفهوم الفعالية من الميادين العلمية و الاقتصادية و المالية الى التربية و تحديدا في مجال تعليم اللغات الاجنبية، خاصة في استغلال كل الوسائل الممكنة  و المتاحة لاقتصاد الوقت و الجهد. فالحصول على أكبر نسبة من النتائج الايجابية في تدريس و تعليم اللغات الاجنبية و بالتالي اصبح دور معلم اللغات الاجنبية تدريجيا معقدا و دقيقا.               و في يومنا هذا نعتبر تدريس و تعليم اللغات الاجنبية تحت زاوية الفعالية و نعني بها اعتبار و تقييم كل صغيرة و كبيرة تخص المتعلم و المعام في ان واحد,  لان تعليم اللغات الاجنبية ليس حصر المفردات و القواعد اللغوية و تعلم اللغة ايضا  ليس انشاء نظريات لسانية. و يجب على الاساتذة ان يكونوا على دراية و وعي بكل المعلومات المتعلقة بالمتعلم بما فيها المحيط الاجتماعي الذي يؤثر على المتعلمين  و مختلف طرق التدريس البيداغوجية و الجانب الثقافي و الاجتماعي للغة التي يتم تدريسها و التعرف على المميزات اللغوية التي تساعد على الالهام  بنفسية المتعلم .  و الفعالية في تدريس اللغة تتمركز اكثر على المتغيرات منه على طرق التدريس.     The concept of efficiency has shifted from the scientific, economic and financial domains to education. Basically into the field of foreign language teaching, in terms of exploiting all possible resources at hand to save time and energy, and obtain maximum, successful results in teaching and learning foreign languages. Consequently the role of a foreign language teacher has become more and more complex and sophisticated.      Nowadays we view teaching and learning foreign languages under the angle of efficiency. The “how much” of everything, because FLT is much more than listing vocabulary items and setting grammar rules. Language learning is not also a matter acquiring a system of linguistic formulas.     Teachers should be aware that they must be well versed in the broad background knowledge of the learners’ social environment that influences their students. Different pedagogical teaching; social and cultural aspects of the language being taught, relevant techniques to decode psychological characteristics of the learners.     In efficiency language teaching is rather centred on variables than methods.